Cluster Formation in a Filamentary Cloud: The Case of the Stellar Cluster NGC 2316 - Saurabh Sharma; Aayushi Verma; Kshitiz Mallick; Lokesh K. Dewangan; Harmeen Kaur; Ram Kesh Yadav; Neelam Panwar; Devendra K. Ojha; Tarak Chand; Mamta Agarwal (The Astronomical Journal, 2024)
We present a multiwavelength analysis of the star cluster NGC 2316 and its surroundings. We estimated the physical parameters of the NGC 2316 cluster, including its shape (elongated), size ( R _cluster = 0.4 pc), distance (1.3 ± 0.3 kpc), and minimum reddening ( A _V = 1.55 mag). We discovered two massive stars (B2.0V-B1.5V, age ∼12 Myr) embedded ( A _V = 4 mag) within this cluster. The cluster region still forms young stars even though the most massive star was born ∼12 Myr ago. We also found evidence of positive feedback from these massive stars. We identified a cold gas/dust lane extending westward from the cluster. The western end of the dust lane seems to favor low-mass star formation, whereas the cluster end favors bit massive star formation, which seems to have started earlier than the western end. We found an elongated molecular cloud in this region, characterized by numerous filamentary structures. The morphology of the filaments, along with position–velocity maps, velocity dispersion maps, channel maps, etc., indicate a coalescence of filaments and a potential longitudinal flow of matter toward the cluster through the western end of the gas/dust lane. This entire region seems to be a Hub-filamentary system (HFS), in which the NGC 2316 cluster is probably the hub and the dark lane is the main filamentary structure. Being the gravity well of this HFS, star formation started first in the NGC 2316 region and went on to the other filamentary nodes.